THE POTENTIAL FOR HUMAN CAPITAL DEVELOPMENT (HCD) THROUGH WAQF FUND - Alam Taifur, Mahfuzul; Ab Rahman , Asmak (Online Journal of Islamic Management and Finance (OJIMF), 2025)
This research aims to address the current contribution of waqf in human capital development (HCD) and to study the potential advantages of utilizing waqf for further enhancements of HCD in Malaysia. The study adopts a qualitative research approach collecting data from the existing literature and it analyzes the data through descriptive and exploratory analysis methods of the study. This study concludes that the use of Waqf for human capital development holds great potential. The study highlights that in Malaysia, Waqf funds have been complimentary financial supports in enhancing various sectors such as education, skills development and training, healthcare, social welfare, and business support programs. Various successful stories in Malaysia are the proof that Waqf funds can improve HCD. The study also recommends that authorities, waqifs, and mutawallī (endowment managers) actively channel waqf funds into educational initiatives, healthcare services, training programs, and social welfare activities. In addition, raising awareness and promotional activities regarding waqf can multiply its benefits, thereby maximizing its positive impact on society. This study contributes to the body of knowledge and provides a clear landscape of using waqf funds for HCD. Future research may develop a specific waqf-based HCD model and include a case study.